Rögzített és mediatizált kapcsolati hálók a 21. századi kibertérben - Faragó, László (Acta Scientiarum Socialium, 2015)
Fixed and Mediatized Social Networks in 21st Century Cyberspace The Social Network formed in cyberspace can be considered stable: access paths, fixed points. There is no possibility to disconnect. The matrix has become charged with media content with sustainable dynamics. The Social Network - among other things, specifies the quality of group interaction, which is not dependent on time or space. The key player of the network is the virtual hero.
Keywords: social network; cyberspace; cyberhero; creative minority; inter-group interaction